The effect of digital learning media using the Book Creator application assisted by Canva on the civics learning outcomes of seventh-grade students at MTs Negeri 1 Sidenreng Rappang - Nur Azizah; Usman M; Abd. Kahar (Universitas Muhammadiyah Enrekang, 2025)
Canva on the Civics (PPKn) learning outcomes of seventh-grade students at MTs Negeri 1 Sidenreng Rappang. This research employed a quantitative approach with a One-Shot Case Study design, a type of quasi-experimental research. The variables in this study consisted of Book Creator assisted by Canva as the independent variable and Civics learning outcomes as the dependent variable. The sample comprised 28 seventh-grade students. Data were collected through a test administered at the end of the lesson. Hypothesis testing was conducted using the Wilcoxon Non-Parametric test with SPSS 25.0. The results showed that after the treatment, the students’ scores ranged from 73.33 to 96.67, with an average score of 88.92. Based on the analysis, the working hypothesis (H1) was accepted, and the null hypothesis (H0) was rejected, indicating a significant effect of using the Book Creator application assisted by Canva on Civics learning outcomes. Thus, it can be concluded that digital learning media based on Book Creator and Canva can positively improve students’ understanding and learning outcomes in Civics.